Poor Glycemic Control is Correlated with Reduced Cognitive Function in Type 2 Diabetes Mellitus Patients - Archangela Olivia Eugenia; Achmad Firdaus Sani; Hermawan Susanto; Jongky Hendro Prajitno (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2022)
Introduction: The prevalence of type 2 Diabetes Mellitus (T2DM) in Indonesia is increasing and is known to cause several complications related to the patient's glycemic control. A chronic hyperglycemic state will lead to microvascular injury of the brain resulting in cognitive impairment as one of the complications of T2DM. Therefore, our present study observed the correlation between glycemic control and cognitive impairment in patients with T2DM.Methods: This was an observational study with a cross-sectional design of T2DM patients in endocrine outpatient clinics of Dr. Soetomo General Academic Hospital from October 2020 to March 2021. The subjects were recruited consecutively then categorized into groups with controlled (HbA1c < 7%) and uncontrolled (HbA1c â‰¥ 7%) blood glucose. The cognitive function was evaluated using the AD8 informant-based questionnaire.Results: A total of 43 adult T2DM patients aged < 65 years were recruited. The incidence of cognitive impairment was not significantly different (p=0.127) between controlled and uncontrolled blood glucose groups. However, HbA1c levels were positively and significantly correlated with AD8 scores (p=0.031, R=0.330). Moreover, the duration of T2DM was found to significantly affect cognitive abnormalities in these patients. (p=0.021).Conclusion: Poor glycemic control in T2DM patients increased the risk of developing reduced cognitive function.